Lab protocol using framework analysis to capture practitioners’ perspectives on the usability of virtual reality for sport rehabilitation - Hannah K. M. Tang; Mark J. Lake; Frederic A. Bezombes (PLoS ONE, 2025)
Addressing issues in sport rehabilitation with technology-based applications is becoming more common due to improved technological solutions. This drives the need for evidence-based rationales and decisions; technology features should be informed by expert opinion and practice. The current lab protocol paper proposes the use of the framework analysis (FA), a qualitative data analysis method, for identifying practitioners’ perspectives on technology solutions aimed at aiding athlete rehabilitation. The FA allows data to be analysed in a structured and rigorous process, whilst also allowing for the flexibility associated with qualitative enquiry. Subsequently, this method is being increasingly used in healthcare and nursing research and could be applied in the context of using technology to enhance sport rehabilitation. In the current paper, FA is applied in the context of determining the usability of virtual reality (VR) in sport rehabilitation and obtaining perspectives on VR features necessary for integration into existing rehabilitation practice. The paper includes a worked example, taking it from raw data to a working theme. The use of the current lab protocol led to the identification of interconnected key themes regarding the following VR application features: how the VR application would be delivered, what the VR application would involve, and why, where, and when the VR application would be used. The lab protocol also allowed subthemes to be derived, indicating how these VR features would be met. The findings inform the ongoing development of a VR application designed to assess quick directional change in sports, potentially applied to the treatment of musculoskeletal injury in athletes. The use of the FA to derive this content is susceptible to limitations present in all qualitative data processing, such as reflexivity, the implications of levels of rigour, as well as being a time-consuming process.